An Appraisal System Used in CNN Headline News Coverage of Sean Diddy Comb’s Case: A Discourse Analysis - Zuhroni; Supatmiwati, Diah; Hastuti, Hilda (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study investigates the use of evaluative language in CNN International's headlines reporting on the legal case of American rapper Sean 'Diddy' Combs through the dual theoretical lenses of Martin and White's (2005) Appraisal System and Van Dijk's theory of ideological discourse. Applying a qualitative descriptive method and discourse analysis approach, we analyzed 31 headlines published from September to December 2024 using the Attitude subsystem's three categories: Judgment, Appreciation, and Affect. The findings reveal a striking dominance of Judgment (88%), particularly within the Social Sanction domain, demonstrating CNN's systematic framing of Combs through legal and moral evaluations. Appreciation (8%) and Affect (4%) appear minimally, relegated to passing references to cultural influence or emotionally charged victim quotes. This evaluative pattern aligns with Van Dijk's concept of ideological bias in media discourse, showing how CNN's linguistic choices construct a criminalized image of Combs before legal resolution. The analysis demonstrates how 88% Judgment-based language, predominantly negative, reinforces dominant moral discourses while marginalizing Combs' cultural contributions (Appreciation) and emotional complexity (Affect). These findings illuminate the media's power to shape public perception through strategic linguistic framing, highlighting the need for critical engagement with news discourse, particularly in high-profile cases where media narratives may precede judicial outcomes.